Estanatos de cálcio (casno3) dopados com Fe3+, Co2+ ou Cu2+ Aplicados na fotodegradação de Remazol Amarelo Ouro E na redução de NO com CO ou NH3 - Santos, Guilherme Leocárdio Lucena dos (2017)
Calcium stannate, CaSnO3, is orthorhombic perovskite-type that presents technological applications as catalysts and photocatalysts. In this work, undoped CaSnO3 and doped with Fe3+, Co2+ or Cu2+ were obtained by the modified Pechini method and applied in photodegradation of the textile dye Remazol Golden Yellow and as catalysts in the reduction reaction of nitrogen monoxide (NO). Furthermore, these materials were deposited on the ZrO2 support or Pd2+-doped or Pd impregnated and evaluated in the reduction of NO with CO and NO with NH3. The catalysts were characterized by thermogravimetric analysis (TG/DTA), X-ray diffraction (XRD), ultraviolet-visible spectroscopy (UV-Vis), infrared spectroscopy (IR), Raman spectroscopy, analysis of the surface area by the BET method, scanning electron microscopy with field emission (FE-SEM) and transmission electron microscopy (TEM). XRD patterns showed a small change in the long range-order for the doped samples due to partial substitution of cations. The Raman spectra indicated that the incorporation of Fe3+, Co2+ and Cu2+ in the CaSnO3 lattice promoted a symmetry breaking, which was confirmed by the change of the band gap values of the samples. The photocatalytic tests of RNL dye were performed in the reactor using a UVC lamp (λ = 254 nm). The catalytic tests were carried out in a reactor containing a gaseous mixture with stoichiometric amounts of nitrogen monoxide (NO) and carbon monoxide (CO) in helium in the temperature range of 300 °C to 700 °C or in a reactor containing a mixture of NO and ammonia (NH3) in helium in the temperature range of 250 °C to 500 °C. The results of the photocatalytic evaluation showed that CaSnO3 doping with transition metals increased the photocatalytic efficiency of the material, especially for the Cu2+ (76% of discoloration), which was related to the while the decrease in the intensity of the photoluminescence spectrum as a function of doping. The catalytic tests of NO with CO showed that Co2+ and Cu2+-doped perovskites showed 100% of conversion, at temperatures above 500ºC. The palladium impregnation promoted the conversion of NO with CO throughout the evaluated temperature range, but it did not favor the reaction of NO with NH3, probably due to the oxidation of NH3 by Pd. The perovskite deposited on the ZrO2 support showed the best catalytic conversion values. The results of FEG and TEM confirmed the deposition of the active phase on the ZrO2 support and indicated the formation of core@shell systems.